Ranger perceptions of the role of local communities in providing actionable information on wildlife crime. Issue 6 (9th April 2020) - Anagnostou, Michelle; Mwedde, Geoffrey; Roe, Dilys; Smith, Robert J.; Travers, Henry; Baker, Julia
Abstract: Wildlife crime in protected areas remains a major challenge to conservation. However, little is known about the role of local communities in providing information on illegal activities to help improve law enforcement efforts in protected areas. As an initial exploration of this complex topic, we aimed to understand the perceptions of law enforcement authorities working directly with local communities on the conditions under which local people provide information to park rangers, using Murchison Falls Protected Area in Uganda as a case study. We used semi‐structured interviews and questionnaires to understand the perceptions of staff from the Uganda Wildlife Authority and nongovernmental organizations. There was consensus among participants that people who provide information are those who have trusted relationships with rangers; interact regularly with community outreach rangers (either formally through community programs or informal socializing); and believe that the protected area benefits them and their community. All respondents believed that information provided by local people can enable the success of wildlife crime investigations, but that associated ethical issues must be addressed. This study indicates that engaging communities in protected area conservation is crucial for law enforcement efforts to be effective in addressing wildlife crime.